ANALISIS KESULITAN SISWA DALAM MEMPELAJARI FAKTOR PERKALIAN, KOEFISIEN, KONSTANTA, SUKU, DAN SUKU SEJENIS - Mika Ambarawati (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2019)
The purpose of this study is to describe students' learning difficulties in studying variables, constants, coefficients, the factors, types of parts, similar tribes, and the tribes do not like. This research is a descriptive study with qualitative approach. This research is a descriptive study with qualitative approach. The subject of this study consisted of three students of class VII A SMP Muhammadiyah 1 Kartasura. The instrument used was a booklet multiplication factor, coefficients, constants, parts, and similar parts and pieces of interviews. Data were analyzed using the concept of Miles and Huberman. The results showed: (1) students have difficulties in understanding the concepts and definitions of the types of parts, multiplication factors, the tribes of similar or not similar tribes, tribal, constants, variables, and the coefficient of the algebra. (2) students have difficulty in classifying the algebra by type tribe. (3) students have difficulty in distinguishing factor of the algebra and multiplication factor numbers. (4) students have difficulty in differentiating the tribes of similar or not similar and why. (5) students' difficulties in classifying the tribe, constants, variables, and the coefficient of the algebra.